Bruxism – contemporary knowledge about the disorder and therapeutic possibilities - Rusin, Bartosz; Wójcik, Alicja; Pakaszewski, Wojciech; Ziomko, Bartłomiej; Smulewicz, Klaudia (Journal of Education, Health and Sport, 2022)
Introduction: bruxism is a parafunction characterized by excessive activity of the masticatory muscles, consisting in grinding, or clenching of the teeth. The etiology of bruxism is multifactorial. Carefully collected history and additional tests enable correct diagnosis. There is no single method that is completely effective in treating bruxism. It is important to make the patient aware of the disorder, it’s possible consequences, and the need for treatment. Aim of the study: approximation of the bruxism profile, drawing attention to the prevalence of the disorder and the need for early diagnosis, as well as discussing the current therapeutic options Material and methods: the authors reviewed the literature on bruxism in terms of its causes, epidemiology, symptoms, diagnosis, and treatment Conclusions: Correct, short-term diagnosis and application of appropriate treatment may inhibit the development of functional disorders of the masticatory system.